2000
DOI: 10.2486/indhealth.38.280
|View full text |Cite
|
Sign up to set email alerts
|

Study on Work Load of Matrons under Shift Work in a Special Nursing Home for the Elderly.

Abstract: In order to find out the work load of matrons under shift work in a special nursing home for the elderly (SNH), six healthy female matrons volunteered to participate in the present study. For each subject, care working time, heart rate, walking steps, estimated energy expenditure and working time in different postures were determined during day shift work (540 min) and night shift work (960 min). Although the time on duty, working and recess were significantly longer in night shift work than day shift work, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 8 publications
(17 reference statements)
1
12
0
2
Order By: Relevance
“…(2001) reported a reverse correlation between %HR max and cardiorespiratory fitness among hospital nurses. Regardless of cardiorespiratory fitness status, positive correlations between HR and the strenuousness of patient handling activities were seen in a number of studies (Wakui 2000, Nuikka et al. 2001, Wakui et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2001) reported a reverse correlation between %HR max and cardiorespiratory fitness among hospital nurses. Regardless of cardiorespiratory fitness status, positive correlations between HR and the strenuousness of patient handling activities were seen in a number of studies (Wakui 2000, Nuikka et al. 2001, Wakui et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of nursing activities (Irimagawa et al. 1991, 1993, Garcia 1993, Irimagawa & Imamiya 1993a, Wakui 2000, Wakui et al. 2002) measured EE spent at work by tracking heart rates (HRs) via the HR–oxygen uptake relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the more dependent the patient, the higher the prevalence of musculoskeletal disorders among their caring staff (2). Employment within a nursing home usually involves repetitive work, working fast and expending significant amounts of energy (3)(4)(5)(6). Staff caring for the elderly are often fatigued after work and may have high strain complaint rates (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that nurses spend approximately 31% of their shift time in patient's rooms and 91% doing nursing tasks such as documentation and charting (35%), medication administration (17%) and direct patient care (19%) 123 . As such, studies that have objectively measured nurses' physical activity while they are conducting these tasks primarily report that they spend most of their shifts standing and in slow walking 124,125 .…”
Section: Occupational Physical Activitymentioning
confidence: 99%